Assessment of the effectiveness of the psychological rehabilitation of children and parents who were patients of the National Children's Specialized Hospital "OKHMATDYT" of the MOH of Ukraine in Latvia - Tokarchuk, Anastasia; Anoprienko, Olena; Dambina, Liene; Zhovnir, Volodymyr (Psychosomatic Medicine and General Practice, 2025)
Relevance. The full-scale invasion has become an extremely serious challenge for every citizen of Ukraine. Children and adolescents have become one of the largest categories of high-risk groups in terms of age, as they are one of the most vulnerable categories of the population. Because the still unformed psyche can be affected many times more and bring negative changes in the future throughout life. Constant long-term stress due to the existing danger, the need to leave home, disruption of the usual way of life and the breakdown of social ties negatively affect the mental state of any person. One of the key psychological problems that arise as a result of hostilities is high anxiety, which is associated with the difficulty of adapting to sudden changes, or complete maladjustment, apathy and depression. Most face the issue of switching to distance learning, the need to attend new schools due to resettlement, or integrate into foreign educational institutions, combining two educational programmes in parallel. All of these circumstances create a wide range of stressful challenges that children experience while studying at school and in their environment. For this reason, psychological rehabilitation should combine a variety of methods in a combination of individual therapy and group work. Materials and methods. The Phillips School Anxiety Test to determine the level of school anxiety was used for children and teenagers. Also, the level of self-esteem was examined using the Dembo-Rubinstein method. A psychodiagnostic study was conducted for parents using special techniques.: Depression Scale PHQ-9; Generalized Anxiety Disorder Questionnaire GAD-"; Hospital Anxiety and Depression Scale HADS, quality of life was assessed using the Quality of Life Assessment Scale. Results. 147 children (aged 3 to 14 years) participated in the study: 103 children aged 7-14 years and 44 children aged 3-6 years; 113 parents participated in the study. Parents were examined for levels of anxiety and depression before and after rehabilitation using the methods PHQ-9 Depression Scale, GAD-7 Generalized Anxiety Disorder Questionnaire, and HADS Hospital Anxiety and Depression Scale, and quality of life was also assessed using the Quality of Life Assessment Scale. The children's level of school anxiety was determined before and after rehabilitation using the Phillips School Anxiety Test, and the level of self-esteem was also examined using the Dembo-Rubinstein method. Statistical analysis was performed in Jamovi v. 2.3. Descriptive statistics methods were used. Statistical probability was determined using the chi-square and ANOVA methods. As a result of psychological rehabilitation, the emotional state of the children has significantly improved. Anxiety levels decreased by 12.4% after undergoing rehabilitation. Self-esteem indicators also increased significantly, with most children having high (42.7%) and average (43.7%) self-esteem, which may indicate that children have acquired a resource of stress resistance after undergoing psychological rehabilitation and acquiring stress-coping skills. There are also significant indicators of improvement in the emotional state of the children's parents. According to the HADS scale, anxiety decreased by 32.25%, and depression by 24.5%. According to the PHQ-9 scale, depression scores decreased by 12.46%, and anxiety scores, according to the GAD-7 scale, decreased by 14.48%. Such indicators show the high effectiveness of the psychological rehabilitation program for children and their parents in Latvia. Conclusions. Organizing and conducting psychological rehabilitation of children in a safe environment using various psychotherapeutic methods, physical therapy, and cultural activities provide positive content and a resource for the psychological resilience of children and their parents. In difficult wartime, an essential component is the psychological rehabilitation of vulnerable categories of children, such as children with chronic somatic or surgical pathologies.